APLIKASI MANAJEMEN DAN MONITORING UNTUK KEAMANAN PADA JARINGAN HOTSPOT - Sadam Husen; Raisul Azhar (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2016)
STMIK Bumigora has fve internet hotspot access point which can be used by students. Fifth hotspot wireless access point includes faculty, labs, students, faculty and for management purposes. The use of wireless networks for internet access led to the illegal activities that can not be monitored by the network administrator. Activity is mainly on the use of the router that serves as a proxy router connected directly to the ISP (Internet Service Provider). Illegal activities are often done by the students is trying to log into any network devices using bruteforce method. Techniques used include using remote access such as ssh, telnet and ftp. In addition, the activity of port scanning is often performed by the students to observe the security gaps that are still weak in a hotspot, especially at the port still open on the network. To overcome this problem, researchers built an application that is capable of managing and monitoring security hotspots making it easier for network administrators to take action against such illegal activities. Research method used is SDLC, in which the system is intended to develop a system that has existed previously in PUSTIK STMIK Bumigora Mataram